Proses Perencanaan dalam Penyusunan Rencana Kerja Pemerintah Daerah (RKPD) (Studi pada Bappeko Mojokerto) - Yusnita, Febriana Panca (Jurnal Ilmiah Administrasi Publik, 2020)
As a process, development is carried out continuously and well planned which covers all aspects of life in the country such as politics, economy, social culture and defense and security. Development is a way to achieve the ideals of independence stated in the Preamble of Undang-Undang Dasar 1945 that must be carried out carefully, effectively, efficiently and integrated. In implementing development, each local government requires accurate planning and expected to be able to evaluate development. The main key to the success of development lies in the quality of the development planning. One example of a development planning document is Rencana Kerja Pemerintah Daerah (RKPD). The objectives of this study is to describe and analyze the process of preparing RKPD. This study shows that the planning process in the preparation of RKPD has gone through the stage of problem diagnosis; formulation of objectives; and forecasts and projections. As for the alternative development stage; feasibility analysis; and evaluation, not done yet.